The Paradox of Pain Experiences - Murata, Junichi (Investigaciones Fenomenológicas, 2021)
There are few things in our lives we dislike or hate so strongly as pain. On the other hand, the symptoms of the patients suffered from so-called congenital analgesia teach us that if we are deprived of the ability to feel pain, our lives would be unbelievably miserable and disastrous. In this way, if we try to understand the meaning and the value of pain, it seems we immediately find a paradox. The paradoxical character of pain is reflected in philosophical discussions between subjectivist’s and objectivist’s view of pain. In this paper, I try to show that the seemingly paradoxical character emerges because we are obsessed by groundless prejudice that the concept of pain must have one definite single meaning and that if phenomena of pain can be understood as multidimensional, the various characteristics of pain can be interpreted as various aspects of multi-dimensional pain experiences. Hay pocas cosas en nuestras vidas que nos desagraden u odiemos tan fuertemente como el dolor. Por otro lado, los síntomas de los pacientes que padecen la llamada analgesia congénita nos enseñan que, si nos privamos de la capacidad de sentir dolor, nuestras vidas serían increíblemente miserables y desastrosas. De esta manera, si tratamos de comprender el significado y el valor del dolor parece que encontramos inmediatamente una paradoja. El carácter paradójico del dolor se refleja en discusiones filosóficas entre la visión del dolor subjetivista y objetivista. En este trabajo, trato de mostrar que el carácter aparentemente paradójico surge porque estamos obsesionados por el prejuicio infundado de que el concepto de dolor debe tener un único significado definido; y que, si los fenómenos de dolor pueden entenderse como multidimensionales, las diversas características del dolor pueden ser interpretadas como varios aspectos de expe-riencias de dolor multidimensionales. Palabr